Immigrazione e sicurezza. Il ruolo dello SPRAR nella metropoli di Roma e in alcuni comuni medi italiani - Ferretti, Daniele (Antropologia Pubblica, 2017)
In the last few years Italian cities are playing a key role to face the arrival of migrants on the Italian coasts. The foreign presence can have a different impact within urban contexts. On one side, it can promote the social, economic and cultural development but, on the other one, we have assisted to the increase of citizens’ insecurity and the development of urban conflicts. Thus, in order to investigate the impact of reception policies in the Italian cities, the paper focuses on the reception paths of asylum seekers and refugees within System of Protection of Asylum Seekers and Refugees (SPRAR) in the suburbs of “Tor Sapienza” (Rome) and in three Italian medium size cities: Savona (North of Italy), Pesaro (Centre of Italy), Matera (South of Italy).